2020
DOI: 10.1183/13993003.03091-2020
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of obstructive sleep apnoea discovers a strong association with cardiometabolic health

Abstract: There is currently limited understanding of the genetic aetiology of obstructive sleep apnoea (OSA). We aimed at identifying genetic loci associated with OSA risk and to test if OSA and its comorbidities share a common genetic background.We conducted the first large-scale genome-wide association study of OSA using FinnGen Study (217 955 individuals) with 16 761 OSA patients identified using nationwide health registries.We estimated 8.3% [0.06–0.11] heritability and identified five loci associated with OSA (p&l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 51 publications
1
59
0
Order By: Relevance
“…This reflects a similar prevalence of OSA diagnoses in COVID-19 infected as in the normal population in FinnGen, where prevalence is 8%. 18 Ninety-one (20.4%) patients required hospitalisation (36.3% male, mean age 65.9 years) including 19 patients with OSA (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…This reflects a similar prevalence of OSA diagnoses in COVID-19 infected as in the normal population in FinnGen, where prevalence is 8%. 18 Ninety-one (20.4%) patients required hospitalisation (36.3% male, mean age 65.9 years) including 19 patients with OSA (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Third, we attempted to examine the relationship between sleep apnoea and depression in a population using MR. However, studies have reported sleep apnoea heritability estimates of 8.3% (95% CI 6–11%), whereas there are only five SNPs associated with sleep apnoea (p<5.0×10 −8 ), including three SNPs in UK Biobank [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early EHR analyses used International Classification of Disease (ICD) codes for sleep apnea phenotyping. 27 , 28 ICD data are largely collected for clinical and billing purposes. ICD-derived disease diagnoses are often used when ruling out a given disease through a billed procedure such as a sleep examination whether or not the patient is found to have that condition.…”
Section: Background and Significancementioning
confidence: 99%